1994
DOI: 10.1007/bf03344963
|View full text |Cite
|
Sign up to set email alerts
|

A cross-over study with the two novel dopaminergic drugs cabergoline and quinagolide in hyperprolactinemic patients

Abstract: Cabergoline and quinagolide, two new dopamine agonist drugs with long-lasting activity, are currently under investigation for the treatment of hyperprolactinemia. At present, studies comparing these drugs for tolerability and efficacy in the same patients are lacking. It was our aim to make such a comparison in an open randomized cross-over trial. Cabergoline (0.5 mg twice weekly) and quinagolide (75 micrograms once daily) were given orally. Each drug was administered for 12 weeks. Treatment with the second dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Giusti et al (233) compared once-daily quinagolide (0.075 mg) with twice-weekly cabergoline (0.5 mg) in 12 patients enrolled in a randomized cross-over study where treatment with the second dopamine agonist was initiated after the recurrence of hyperprolactinemia. Nine patients completed both treatment cycles; the clinical effects were similar with the two drugs and, interestingly, only one patient remained resistant to both dopamine agonists.…”
Section: Quinagolidementioning
confidence: 98%
“…Giusti et al (233) compared once-daily quinagolide (0.075 mg) with twice-weekly cabergoline (0.5 mg) in 12 patients enrolled in a randomized cross-over study where treatment with the second dopamine agonist was initiated after the recurrence of hyperprolactinemia. Nine patients completed both treatment cycles; the clinical effects were similar with the two drugs and, interestingly, only one patient remained resistant to both dopamine agonists.…”
Section: Quinagolidementioning
confidence: 98%
“…Treatment with the second dopamine agonist was initiated after the recurrence of hyperprolactinaemia; nine patients completed both treatment cycles. In this study, the clinical effects were similar with both cabergoline and quinagolide and, interestingly, only one patient remained resistant to both dopamine agonists (53). In a study of 26 children or adolescents with prolactinomas, 16 were considered resistant or intolerant to bromocriptine (52).…”
Section: Efficacy Of Quinagolide Compared With Cabergolinementioning
confidence: 51%
“…Therefore, in this study, quinagolide and cabergoline normalised prolactin levels in the majority of patients after 12 months of treatment, but recurrence of hyperprolactinaemia was observed in all patients with macroprolactinomas withdrawn from cabergoline and quinagolide (21). In another randomized cross-over study, 12 patients received either once-daily quinagolide (0.075 mg) or twice-weekly cabergoline (0.5 mg) for 12 weeks (53). Treatment with the second dopamine agonist was initiated after the recurrence of hyperprolactinaemia; nine patients completed both treatment cycles.…”
Section: Efficacy Of Quinagolide Compared With Cabergolinementioning
confidence: 62%
“…There are not many data comparing these two novel dopaminergic drugs. In a cross-over trial including 12 hyperprolactinemic women, Giusti et al [14] observed a normalization of serum PRL levels in 10 patients during CAB therapy (0.5 mg twice weekly) and in 6 during CV treatment (75 µg once daily.) In a recent study by Colao et al [5], 13 of the 20 patients resistant to 600 µg CV daily responded to low doses of CAB (0.5–1 mg weekly).…”
Section: Discussionmentioning
confidence: 99%